Art incorporated - Stallabrass, Julian (Oxford University Press, 2004)
Stallabrass notes that the spectacular crash of 1989 profoundly changed the character of contemporary art, shattering the art-world's self-importance and producing a reaction against art that engaged with theory and politics, in favor of art that set out to awe, entertain, and be sold. He describes the growth of biennials and other art events across the globe in the 1990s, the construction of new museums of contemporary art, and the expansion of many museums already in existence